Long-term persistence to low-dose aspirin for cardiovascular prevention in routine clinical practice in United Kingdom and Germany. (25th November 2020) - Vora, P; Soriano-Gabarro, M; Russell, B; Morgan Stewart, H
Abstract: Background: Low-dose aspirin is effective in the prevention of ischemic vascular events and studies have shown a preventative effect on colorectal cancer (CRC). Discontinuation of low-dose aspirin is associated with increased risk of ischaemic vascular events. However, data on long-term persistence to low-dose aspirin from routine clinical practice are limited. Purpose: To assess the long-term persistence to low-dose aspirin therapy in the primary and secondary cardiovascular (CVD) prevention population Methods: This retrospective cohort study used data from United Kingdom (UK) – The Health Improvement Network database and Germany (DE) – IQVIA Disease Analyzer and analyzed using an adaptation of Observational Health Data Sciences and Informatics (OHDSI) ATLAS Tool. Patients 18 years or older, with at least two prescriptions of low-dose aspirin (75–100mg) within the first year of index date during the study period between 2007 and 2018, and with at least 12 months of observation before and after the index date were included in the study. The patients with a CVD diagnosis or a CABG/PCI procedure before the index date or a prescription of dual antiplatelet at index date were classified as secondary CVD prevention. The remaining patients were classified as potential primary CVD prevention. The index date was first prescription of low-dose aspirin. Persistence was calculated if the gap between two prescriptions exceeds 60 days. Patients with such gaps still receiving prescription after 60 days were plotted based on the number of gaps identified during the follow-up and if no prescription was recorded then they were considered discontinued. Results: The total number of patients receiving low-dose aspirin was 327, 806 (183, 089 in UK and 144, 717 in DE with up to 10 years of follow-up). A total of 112, 887 and 101, 704 received low-dose aspirin for secondary CVD prevention; 70, 202 and 43, 013 potentially for primary CVD prevention in UK and DE, respectively. Persistence at two years with a few gaps was 67% and 59% in UK and DE for secondary CVD prevention; 57% and 53% for primary CVD prevention, respectively. With multiple Gaps, 50% and 36% still receive prescription low-dose aspirin for 10 years in UK and DE, respectively for secondary CVD prevention. For Primary prevention, 36% and 32% receive prescription of aspirin for 10 years with multiple gaps in UK and DE (Figure). Conclusion: After the initial drop in persistence the patients tend to continue their low-dose aspirin treatment for long-term, although with multiple gaps. Overall, the persistence was higher in secondary compared to primary CVD prevention. Improving persistence to low-dose aspirin therapy in the initial years may help in continuity of their treatment over long-term. Persistence might be underestimated due to potential over the counter use of low-dose aspirin. Funding Acknowledgement: Type of funding source: Private company. Main funding source(s): Bayer AG